IMPACT OF COVID-19 PANDEMIC ON WORK SPIRIT BASED ON ISLAMIC WORK ETHICS OF MSME ENTREPRENEURS PRODUCE CRACKERS AND SHREDDED FROM CHIKEN BONE IN SAWOCANGKRING, SIDOARJO - Saifudin; Ani Faujiah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The SMEs affected by the Covid-19 pandemic, namely crackers and shredded chicken bone SMEs in Sawocangkring, Sidoarjo. The impact was purchasing power decrease so that production was carried out only the orders. The MSME owner (Yuni) has a work spirit based on an Islamic work ethic and can be seen from obtaining a halal certificate. The purpose of this study was to determine the impact of the Covid-19 Pandemic on Yuni's Islamic work ethic spirit. This research method is descriptive qualitative using purposive and purposive-snowball sampling techniques. Yuni's motivation: wanted to increase family income, prepare children's educational supplies, and intend to worship. The Covid-19 pandemic caused Yuni had surrender attitude, inconsistent with the Islamic work ethic. Yuni still has working spirit based on other Islamic work ethic, including hard worker; smile and be friendly, when serving customers; considering the selling price; Honest; paying attention to the quality of goods; as well as professionalism. Yuni can resolve the problems with look for solution to overcome the attitude of giving up.